qt=uy

Rewrite the equation as uy=qt.

uy=qt

Multiply each term by a factor of 1 that will equate all the denominators. In this case, all terms need a denominator of yt. The uy expression needs to be multiplied by tt to make the denominator yt. The qt expression needs to be multiplied by yy to make the denominator yt.

uy⋅tt=qt⋅yy

Multiply the expression by a factor of 1 to create the least common denominator (LCD) of yt.

u(t)

Multiply u by t.

utyt=qt⋅yy

Multiply the expression by a factor of 1 to create the least common denominator (LCD) of yt.

q(y)

Multiply q by y.

utyt=qyyt

utyt=qyyt

Since the expression on each side of the equation has the same denominator, the numerators must be equal.

ut=qy

Rewrite the equation as qy=ut.

qy=ut

Divide each term in qy=ut by q.

qyq=utq

Cancel the common factor of q.

Cancel the common factor.

qyq=utq

Divide y by 1.

y=utq

y=utq

y=utq

Solve for y q/t=u/y